KATOBA IN MUNA SOCIETY - Hayani, Aida; Prasojo, Zaenuddin Hudi (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2021)
Abstract: Katoba is one tradition of the Muna Community. It still preserved and practiced. Especially in Muna society, it has been adapted into Islam practice. This study Aimed to know how katoba are believed and practiced and then become one of a religious creed which, originally is not purely derived from Islamic teaching. This study used a case study. Islam has Universalism concept that is able to converge and fuse with various civilizations and culture, this makes Islam accepted in many nations and civilizations. Muna people believe that katoba is one of the rituals associated with religious belief. Because it is consist of several religious values which must be executed, such as 2 (two) aspects as follow: firstly; the Actor of katoba should have a good understanding of the religion. Secondly, the moment to do katoba is when the children become approaching puberty (6-12 age). Katoba is considered to be closely related to Islam, so it becomes a public belief.Abstrak: Katoba merupakan salah satu tradisi masyarakat Muna yang masih dilestarikan dan dipraktikkan, khususnya di masyarakat Muna, telah diadaptasi ke dalam praktik Islam. Kajian ini bertujuan untuk mengetahui bagaimana katoba diyakini dan diamalkan kemudian menjadi salah satu akidah agama yang semula tidak murni bersumber dari ajaran Islam. Penelitian ini menggunakan studi kasus. Islam memiliki konsep Universalisme yang mampu menyatu dan melebur dengan berbagai peradaban dan budaya, hal ini membuat Islam diterima di banyak bangsa dan peradaban. Orang Muna percaya bahwa katoba adalah salah satu ritual yang terkait dengan kepercayaan agama. Karena didalamnya terkandung beberapa nilai religi yang harus dijalankan, seperti 2 (dua) aspek sebagai berikut: pertama; Pelaku katoba harus memiliki pemahaman yang baik tentang agama. Kedua, saat melakukan katoba adalah saat anak mendekati pubertas (6-12 tahun). Katoba dianggap sangat erat kaitannya dengan Islam, sehingga menjadi kepercayaan masyarakat.